When will a victim be secondarily victimized? The effect of observer’s belief in a just world, victim’s innocence and persistence of suffering - Correia, I. (2003)
According to the belief in a just world (BJW) theory, the most threatening victim for the observers' BJW is the innocent victim whose suffering persists. Consequently the innocent victim whose suffering persists should be more secondarily victimized by high-BJW participants than by low-BJW participants. However, research has never systematically tested this basic prediction of the theory. In these two studies we tried to determine the impact of the observer's BJW, the victim's innocence, and the persistence of the victim's suffering on secondary victimization. In study 1, an interaction between BJW and victim's innocence was found on the attractiveness of the victim. In study 2, an interaction between BJW, victim's innocence, and persistence of suffering was found on the derogation of the victim.